ANALYSIS OF CHEMICAL AND MICROBIAL CHANGE DURING STORAGE OF OVERRIPE TEMPEH POWDER AS SEASONING MATERIAL - Tia Raisha Hassanein; Elisabeth Kartika Prabawati; Maria Dewi Puspitasari Tirtaningtyas Gunawan-Puteri (Chemical Engineering Diponegoro University, 2015)
Tempeh and other soy-derived products are historically and currently some of the most important foods in the Asian region where diets remain predominantly plant-based. Overripe tempeh (tempe semangit) is a term used for over-fermented tempeh with pungent odor and darkening appearance commonly used in Javanese cuisine. Unique taste and odor of overripe tempeh lead to the exploration of its potencies as condiment, which may add the nutritional, safety and economic values of tempeh. In this research, overripe tempeh is made into powder for better appearance and availability. Oven drying at 60oC and freeze drying were applied to the overripe tempeh until it reached moisture content below 5%, followed by subsequent crushing into powder using electric grinding machine. As seasoning material, the tempeh powder and overripe tempeh powder were then analyzed for their stability. Observations in chemical and microbial changes during storage were also applied to selected product during storage. Parameters observed during the research are: moisture content, protein content, acid content, total microbial count and total coliform. Oven dried overripe tempeh (S60) has higher moisture content but lower in acid content, total microbial count and total coliform compared to freeze dried overripe tempeh (SFD).